2011
DOI: 10.1128/jb.00007-11
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of a Dominant, Multidrug-Resistant Neisseria gonorrhoeae Strain, TCDC-NG08107, from a Sexual Group at High Risk of Acquiring Human Immunodeficiency Virus Infection and Syphilis

Abstract: Neisseria gonorrhoeae infection is the second major cause of sexually transmitted diseases worldwide. Development of resistance to multiple classes of antimicrobials in N. gonorrhoeae has compromised treatment and disease control. Herein, we report the availability of the draft genome sequence of a multidrug-resistant N. gonorrhoeae isolate, TCDC-NG08107, which spread in groups of men who have sex with men (MSM) in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…gonorrheae encodes XerC and XerD homologs as well as two FtsK homologs (19). We cloned and purified tagged versions of XerC Ng and XerD Ng (Methods, SI Text, and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…gonorrheae encodes XerC and XerD homologs as well as two FtsK homologs (19). We cloned and purified tagged versions of XerC Ng and XerD Ng (Methods, SI Text, and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Illumina reads were mapped to a reference strain, TCDC-NG08107 (GenBank accession number NC_017511.1), 16 using SMALT. Single nucleotide polymorphisms (SNPs) were called (ie, filtered to determine the working set of SNPs from all candidate sites) according to previous parameters 17 .…”
Section: Methodsmentioning
confidence: 99%
“…We then used Kraken to search all of the sequences placed on chromosomes 1 through 10, as a quality check on our method. We did not expect any of these contigs to match bacteria, but we unexpectedly found 2,885 small contigs that seemed to align in part to a single bacterial genome, Neisseria gonorrhoeae, strain TCDCNG08107 (Chen et al 2011). This bacterium is a human specific pathogen, and it seemed highly unlikely that it had contaminated the original DNA used for sequencing.…”
Section: Resultsmentioning
confidence: 93%
“…In an effort to determine the source of these foreign sequences in the TCDCNG08107 genome (Genbank accession CP002440), we examined the original publication (Chen et al 2011) and the GenBank entry, and found that although the genome was listed as complete in GenBank, Chen et al described an assembly that comprised 180 contigs. Neither the publication nor the GenBank entry contained any information that the gaps had been filled.…”
Section: Resultsmentioning
confidence: 99%